The quality of life of children with attention deficit/hyperactivity disorder: a systematic review - Danckaerts, Marina; Sonuga-Barke, Edmund J. S.; Banaschewski, Tobias; Buitelaar, Jan; Döpfner, Manfred; Hollis, Chris; Santosh, Paramala; Rothenberger, Aribert; Sergeant, Joseph; Steinhausen, Hans-Christoph; Taylor, Eric; Zuddas, Alessandro; et al. (European child & adolescent psychiatry, 2010)
Quality of life (QoL) describes an individual's subjective perception of their position in life as evidenced by their physical, psychological, and social functioning. QoL has become an increasingly important measure of outcome in child mental health clinical work and research. Here we provide a systematic review of QoL studies in children and young people with attention deficit hyperactivity disorder (ADHD) and address three main questions. (1) What is the impact of ADHD on QoL? (2) What are the relationships between ADHD symptoms, functional impairment and the mediators and moderators of QoL in ADHD? (3) Does the treatment of ADHD impact on QoL? Databases were systematically searched to identify research studies describing QoL in ADHD. Thirty six relevant articles were identified. Robust negative effects on QoL are reported by the parents of children with ADHD across a broad range of psycho-social, achievement and self evaluation domains. Children with ADHD rate their own QoL less negatively than their parents and do not always seeing themselves as functioning less well than healthy controls. ADHD has a comparable overall impact on QoL compared to other mental health conditions and severe physical disorders. Increased symptom level and impairment predicts poorer QoL. The presence of comorbid conditions or psychosocial stressors helps explain these effects. There is emerging evidence that QoL improves with effective treatment. In conclusion, ADHD seriously compromises QoL especially when seen from a parents' perspective. QoL outcomes should be included as a matter of course in future treatment studies.